Administrasi Sengketa Pajak dan Persidangan Secara Elektronik (E-Tax Court) - Suatu Tinjauan Pustaka - Supriyadi, Mohammad Wangsit (Politeknik Keuangan Negara STAN, 2024)
One of fundamental principles of judicial power is administering fast, simple, and low-cost justice. This principle is also applicable to Tax Court which is a special court dealing with tax disputes. Notwithstanding, it is mandatory for the Tax Court to implement electronic tax disputes administration and electronic litigation to respond to technological progress in information and technology and also to implement Supreme Court Regulation Number 7 Year 2022. The implementation of e-Tax Court is effective as of July 2023 subsequent the issuance of Chief of Tax Court Regulation Number 1 Year 2023. This research aims to provide an analysis whether the aforementioned regulation supports the implementation of the fundamental principles of judicial power in tax dispute resolution that is to administer fast, simple, and low-cost justice. There is lack of previous literature focusing on tax disputes resolution in the Tax Court. This study employs a literature review methodology upon relevant regulations and existing bodies of literature as well as previous relevant studies. Results show that the implementation of electronics tax disputes administration and tax litigation under the e-Tax Court platform support the implementation of fast, simple, and low-cost justice in resolving tax disputes in the Tax Court.